2007
DOI: 10.1017/s079096670001048x
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine induced stuttering

Abstract: We describe two cases reports, demonstrating an association between clozapine treatment and stuttering. Stuttering in both cases was dose-related and a significant improvement was noted when the dose of clozapine was reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Eight cases of clozapine-induced stuttering have been reported [Hallahan et al 2007;Lyall et al 2007;Begum, 2005;Duggal et al 2002;Supprian et al 1999;Thomas et al 1994]. These occurred at doses ranging between 125 mg [Thomas et al 1994] and 700 mg [Supprian et al 1999] with two authors suggesting a dose-dependent relationship [Hallahan et al 2007;Thomas et al 1994].…”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight cases of clozapine-induced stuttering have been reported [Hallahan et al 2007;Lyall et al 2007;Begum, 2005;Duggal et al 2002;Supprian et al 1999;Thomas et al 1994]. These occurred at doses ranging between 125 mg [Thomas et al 1994] and 700 mg [Supprian et al 1999] with two authors suggesting a dose-dependent relationship [Hallahan et al 2007;Thomas et al 1994].…”
Section: Case Reportsmentioning
confidence: 99%
“…Three case reports associated clozapine-induced stuttering with seizure activity [Begum, 2005;Duggal et al 2002;Supprian et al 1999] and this view is supported by four cases where the use of valproate greatly improved speech difficulties [Lyall et al 2007;Begum, 2005;Duggal et al 2002;Supprian et al 1999], including facial tics as reported by Begum. Three patients went on to have a generalized seizure [Hallahan et al 2007;Duggal et al 2002;Supprian et al 1999].…”
Section: Case Reportsmentioning
confidence: 99%
“…We are aware of 12 previous case reports that have demonstrated an association between clozapine and the development of stuttering [Kumar et al 2013;Grover et al 2012;Horga et al 2010;Krishnakanth et al 2008;Abdelmawla and Frost, 2007;Lyall et al 2007;Hallahan et al 2007;Begum, 2005;Bar et al 2004;Duggal et al 2002;Supprian et al 1999;Ebeling et al 1997].…”
Section: Introductionmentioning
confidence: 98%
“…We are aware of 12 previous case reports that have demonstrated an association between clozapine and the development of stuttering [Kumar et al 2013;Grover et al 2012;Horga et al 2010;Krishnakanth et al 2008;Abdelmawla and Frost, 2007;Lyall et al 2007;Hallahan et al 2007;Begum, 2005;Bar et al 2004;Duggal et al 2002;Supprian et al 1999;Ebeling et al 1997]. Stuttering is a condition in which the flow or fluency of speech is disrupted by involuntary motor events, resulting in the production of repetitive sounds, syllables and/or fragmented or prolonged words and includes both developmental and neurogenic/iatrogenic subtypes [Krishnakanth et al 2008].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation